Phytochemical-based therapeutics from traditional eastern medicine: analgesic effects and ion channel modulation - Kim, Sung Eun; Chung, Geehoon; Kim, Sun Kwang (Frontiers in Pain Research, 2025)
Pain management remains a major challenge in the healthcare system. While synthetic analgesics are widely used for pain management, their effectiveness in managing chronic pain is often limited due to low efficacy or side effects. Thus, there is growing interest in exploring alternative pain relief methods, particularly using medicinal plants from traditional Eastern medicine and their phytochemicals. Previous studies have demonstrated the modulatory effects of various phytochemicals derived from herbal medicine on pain-related ion channels, such as voltage-gated sodium channels (Nav), calcium channels (Ca2+), and transient receptor potential (TRP) channels. Since these ion channels are integral to the transmission and modulation of pain signals, the ability of specific phytochemicals to activate or inhibit these channels presents a promising avenue for the development of novel analgesics. The goal of this review is to merge herbal insights with ion channel research to highlight the potential of natural compounds for safe and effective pain management. In this regard, we summarize the discovery and characterization of pain-relieving phytochemicals from herbal medicine, and we discuss their mechanisms of action and their potential to mimic or enhance the effects of conventional analgesics through ion channel modulation.